2015
DOI: 10.1089/chi.2015.0015
|View full text |Cite
|
Sign up to set email alerts
|

Friends Like Me: Associations in Overweight/Obese Status among Adolescent Friends by Race/Ethnicity, Sex, and Friendship Type

Abstract: The association between friend and adolescent overweight/obese status depended on adolescents' sex, race/ethnicity, and friendship type. Given the similarities among friends, obesity interventions targeting youth, especially white females, should consider involving friends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
6
1
Order By: Relevance
“…Research has repeatedly shown that overweight youth are less likely to be nominated as friends by others [38, 39], and youth of similar weights tend to cluster, suggesting a possible selection effect [40]. Contrary to much of the research in adolescence [24, 41], we did not observe students sorting into friendships based on BMI similarity.…”
Section: Discussioncontrasting
confidence: 99%
“…Research has repeatedly shown that overweight youth are less likely to be nominated as friends by others [38, 39], and youth of similar weights tend to cluster, suggesting a possible selection effect [40]. Contrary to much of the research in adolescence [24, 41], we did not observe students sorting into friendships based on BMI similarity.…”
Section: Discussioncontrasting
confidence: 99%
“…Christakis & Fowler (2007) reveal that individuals of the same sex are more likely to be similarly obese (see also Renna et al, 2008). Loh & Li (2013) and Bruening et al (2015) find this effect as well, but for females only. In contrast, Trogdon et al (2008) find no statistically significant difference between BMI similarities among same-sex compared to opposite-sex friends.…”
Section: Bmi Clustering Among Same-sex Friendsmentioning
confidence: 76%
“…While most studies on BMI clustering among adolescents build on data from the United States (Bruening et al, 2015;Centola & van de Rijt, 2015;Halliday & Kwak, 2009;Renna et al, 2008;Schaefer & Simpkins, 2014;Shoham et al, 2012;Simpkins et al, 2013;Trogdon et al, 2008;Valente et al, 2009), a growing amount of research shows BMI clustering elsewhere, such as Australia (de la Haye et al, 2011a), Canada (Leatherdale & Papadakis, 2011), China (Loh & Li, 2013;Nie et al, 2015), Spain (Mora & Gil, 2013), and the Netherlands (de la Haye et al, 2017). Gwozdz et al (2015) investigate several European countries at once and find BMI clustering in Italy, Cyprus, Hungary, and Estonia.…”
Section: Bmi and Social Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we assumed that weight gain was socially influenced but that weight loss behavior (without direct intervention) was not (12,21). In support of this assumption, research has suggested that obesity-related behaviors of children and youth are influenced by each other and adults (22)(23)(24). Thus, children (ages 6-11) and adolescents (ages [12][13][14][15][16][17][18][19] were assumed to be influenced by other children and adolescents, respectively, as well as by adults (ages 20-39) and middle-aged adults (ages 40-64).…”
Section: Modelmentioning
confidence: 99%